Role of Internet of Things in Smart Passenger Cars (International Journal of Engineering and Computer Science, 2017)
The rapid development of the Internet of Things (IoT) and Smart Things provides an opportunity for the informationization for the automotive industry. Smart Things is another paradigm shift in IT world. Smart Things are the things that are having embedding smartness or intelligence, identification, automation, monitoring and controlling calibre. Smart Things are assisting human life a lot, nowadays without their applications life is becoming cumbersome. The introduction of the concept of the Internet of things in the automotive industry will carry on the unified tracking, monitoring and managing and processing the entire automobile car operation, and has become a new trend. This paper presents the role of Internet of things and the new technologies in making the passenger car smarter. This paper exhibits systematically on Internet, Things, and then explores on Internet of Things and finally Smart Things from researchers’, and corporate perspective. Moreover, this article focuses on the state of Smart Things and its applications. This in turn would help the new researchers, who want to do research in this IoT domain